2008
DOI: 10.1016/j.tetlet.2008.04.121
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of vinyl aziridines and phenyl isocyanate

Abstract: Thermal coupling of vinyl aziridines and phenyl isocyanate was evaluated. Although oxazolidinone products were predominant, some reactions afforded a seven-membered ring heterocycle. When Ni/ IMes was employed as a catalyst, a wider array of vinyl aziridines underwent coupling reactions. The Ni catalyzed reactions generally afforded vinyl imidazolidinones as major products.Keywords phenyl isocyanate; vinyl aziridine; N-heterocyclic carbene; nickel; imidazolidinone; oxazolidinone; tetrahydro- [1,3]diazepin-2-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Despite the fact that vinyl aziridines are increasingly being exploited as versatile building blocks in organic synthesis, the [3+2] cycloaddition of vinyl aziridine with a two‐atom partner has not been well developed . Since 2000, the groups of Alper,, Trost,, Aggarwal, Louie, and Lee demonstrated a series of [3+2] cycloadditions of vinylaziridines with heterocumulenes (e.g., isocyanates, carbodiimides, CO 2 and isothiocyanates, etc. ), thus efficiently delivering diverse five‐membered heterocycles with two heteroatoms.…”
Section: Figurementioning
confidence: 99%
“…Despite the fact that vinyl aziridines are increasingly being exploited as versatile building blocks in organic synthesis, the [3+2] cycloaddition of vinyl aziridine with a two‐atom partner has not been well developed . Since 2000, the groups of Alper,, Trost,, Aggarwal, Louie, and Lee demonstrated a series of [3+2] cycloadditions of vinylaziridines with heterocumulenes (e.g., isocyanates, carbodiimides, CO 2 and isothiocyanates, etc. ), thus efficiently delivering diverse five‐membered heterocycles with two heteroatoms.…”
Section: Figurementioning
confidence: 99%
“…Both thermal and metal-catalyzed reactions have been studied and compared [39], and the thermal coupling was shown to proceed nonselectively, leading to mixtures of regioisomers [42][43][44]. Interestingly, the issue of chemoselectivity was found to depend upon the stereochemistry of the starting alkene.…”
Section: Expansions Into Imidazolidinonesmentioning
confidence: 99%
“…Proposed mechanism for nickel-catalyzed reaction of aziridines with isocyanates[171].In 2008, Louie et al reported on the ring-expansion reaction of vinylaziridines and isocyanates under thermal conditions, using Ni as the catalyst[172]. If no catalyst is added and thermal conditions (100 • C) are used, no imidazolidinon-2-ones are observed, and compounds such as oxazolidinones or seven-membered heterocycles are found in the final reaction mixtures.…”
mentioning
confidence: 99%